Object-oriented modelling of wind turbines and its application for control design based on nonlinear dynamic inversion. Issue 3 (4th May 2017) - Reiner, Matthias J.; Zimmer, Dirk
ABSTRACT: This article presents the object-oriented modelling of wind turbine aero-elastics. The article details the undertaken modelling approach and demonstrates its validity by comparing the results to a domain-specific simulation tool. The resulting object-oriented models can be generically adapted to meet different tasks or combined with models from other domains. Also the combination object-oriented Modelica and functional mock-up interface technology enable a rapid design of nonlinear controllers. As one possible application example, the article presents the model-based design of a corresponding controller. Its goal is to extend the turbine lifetime by reducing the structural loads. To this end, a modern control scheme is proposed that takes full advantage of the underlying object-oriented modelling approach. The controller is based on nonlinear dynamic inversion control methods combined with pseudo control hedging. The controller uses wind speed measurement information to adjust to wind gust load. Simulation-based comparisons to conventional control designs show a large potential reduction of the gust load on the wind turbine using the proposed controller.